Baicalin Protects Mice from Lethal Infection by Enterohemorrhagic Escherichia coli - Zhang, Yong; Qi, Zhimin; Liu, Yan; He, Wenqi; Yang, Cheng; Wang, Quan; Dong, Jing; Deng, Xuming (Frontiers in Microbiology, 2017)
Shiga-like toxin-producing Escherichia coli (STEC) O157:H7 poses grave challenges to public health by its ability to cause severe colonic diseases and renal failure in both human and some animals, such as greyhound dogs. This problem is complicated by the fact that antibiotic treatments of enterohemorrhagic E. coli (EHEC) infections may increase the risk of the hemolytic–uremic syndrome (HUS) in patients. In this study, we found that post-infection use of the natural compound baicalin (BAI) significantly reduces O157:H7-induced lethality and renal damage in mice. Our results establish baicalin as a potentially effective treatment for STEC infections.